Challenges and Opportunities of Big data in Health Care: Afrozah Nadeem - Afrozah Nadeem, Afrozah Nadeem; SUNDUS MUNIR, SUNDUS MUNIR; Syeda Binish Zahra, Syeda Binish Zahra; sadia kousar, sadia kousar (International Journal for Electronic Crime Investigation, 2020)
The term big data is referring to huge amount of structured and unstructured data. The concept of big data is based on three V’s that are volume velocity and verity. Health care industry is produced huge amount of data every day. As all the things and industries become globalized, the health care industry also becomes digitalized. For the purpose to solve the human being health issue the research applies big data technique to analysis the huge amount of data. In this article complete review about using of big data health care industry is presented. The main purpose of this article is to discuss about all the challenges which create hurdle to create opportunities in implementation of big data